Design and preparation of ZnS‐ZnFe2O4: a green and efficient hybrid nanocatalyst for the multicomponent synthesis of 2, 4, 5‐triaryl‐1H‐imidazoles. (23rd May 2019) - Varzi, Zahra; Maleki, Ali
Abstract : In the present work, a new protocol was introduced for the preparation of an efficient hybrid nanocatalyst ZnS‐ZnFe2 O4 via the co‐precipitation method as well as its application in the synthesis of 2, 4, 5‐triaryl‐1 H ‐imidazoles derivatives starting from various aromatic aldehydes, benzil and ammonium acetate under ultrasonic irradiation in ethanol. ZnS‐ZnFe2 O4 was characterized by Fourier transform infrared (FT‐IR) spectroscopy, energy‐dispersive X‐ray spectroscopy (EDS) analysis, scanning electron microscopy (SEM) image, X‐ray diffraction (XRD) pattern and vibrating sample magnetometer (VSM) curve. This method has advantages such as high efficiency of the heterogeneous catalyst, the use of environmentally‐friendly solvent, high yields, short reaction times and easy isolation of the products and chromatography‐free purification. Our outcomes illustrated that the present nanocatalyst with nearly spherical and Cauliflower‐like morphology and average particle size of 36 nm could be applied as an effective and magnetically recyclable catalyst without any significant decreasing of activity. Furthermore, the synergic effect of bimetallic Lewis acids was studied for the synthesis of imidazole derivatives. Abstract : A new magnetic hybrid, ZnS‐ZnFe2 O4 MTMO, was designed, identified and used as an efficient heterogeneous nanocatalyst by a simple procedure for the synthesis of 2, 4, 5‐triaryl‐1 H ‐imidazoles.